PENGARUH PENDEKATAN JOYFUL LEARNING BERBASIS AUGMETED REALITY TERHADAP KECEMASAN MATEMATIKA SISWA: SYSTEMATIC LITERATURE REVIEW - Izatunnisa; Nindiasari, Hepsi; Fathurrohman, Maman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effect of a joyful learning approach based on augmented reality on students' mathematics anxiety through a systematic literature review (SLR) method. Literature searches were conducted systematically using the keywords